Development of the Critical Thinking Toolkit (CriTT): a measure of student attitudes and beliefs about critical thinking - Stupple, Edward J.N.; Maratos, Frances A.; Elander, James; Hunt, Thomas E.; Cheung, Kevin Y.F.; Aubeeluck, Aimee (Elsevier, 2017)
Critical thinking is an important focus in higher education and is essential for good academic achievement. We report the development of a tool to measure critical thinking for three purposes: (i) to evaluate student perceptions and attitudes about critical thinking, (ii) to identify students in need of support to develop their critical thinking, and (iii) to predict academic performance. Seventy-seven items were generated from focus groups, interviews and the critical thinking literature. Data were collected from 133 psychology students. Factor Analysis revealed three latent factors based on a reduced set of 27 items. These factors were characterised as: Confidence in Critical Thinking; Valuing Critical Thinking; and Misconceptions. Reliability analysis demonstrated that the sub-scales were reliable. Convergent validity with measures of grade point average and argumentation skill was shown, with significant correlations between subscales and validation measures. Most notably, in multiple regression analysis, the three sub-scales from the new questionnaire substantially increased the variance in grade point average accounted for by measures of reflective thinking and argumentation. To sum, the resultant scale offers a measure that is simple to administer, can be used as a diagnostic tool to identify students who need support in developing their critical thinking skills, and can also predict academic performance.